A review on insulation materials for energy conservation in buildings. (June 2017) - Aditya, L.; Mahlia, T.M.I.; Rismanchi, B.; Ng, H.M.; Hasan, M.H.; Metselaar, H.S.C.; Muraza, Oki; Aditiya, H.B.
Abstract: In residential sector, air conditioning system takes the biggest portion of overall energy consumption to fulfil the thermal comfort need. In addressing the issue, thermal insulation is one efficient technology to utilize the energy in providing the desired thermal comfort by its environmentally friendly characteristics. The principle of thermal insulation is by the proper installation of insulation using energy-efficient materials that would reduce the heat loss or heat gain, which leads to reduction of energy cost as the result. This paper is aimed to gather most recent developments on the building thermal insulations and also to discuss about the life-cycle analysis and potential emissions reduction by using proper insulation materials.